Pengaruh Metode Pembelajaran Debat Aktif Terhadap Hasil Belajar Siswa SMAN 1 Belitang Hilir - Erni Fatmawati; Imron Setiawan (Universitas Pancasakti Tegal, 2017)
This study aims to determine: 1) Average student learning outcomes using conventional learning methods 2) Average student learning outcomes using active learning methods of debate 3) The difference in the average of student learning outcomes. The approach taken in this research is quantitative approach. The type of research is experimental research, Quasy Experimental Design research design with Nonequivalent control group design. The results showed that: 1) The average learning outcomes of students using conventional learning is in good category with a value of 70.47; 2) The average student learning outcomes using active debate learning are in very good category with a score of 81.17; 3) There are differences in student learning outcomes based on t hitung (-5,429) ≥ t table (2.045) with Sig. (2-tailed) 0.00 ≤ 0.05 so that alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.